O paradoxo do sexo: a sexualidade no pensamento de Jean-Jacques Rousseau - Ferreira Junior, Paulo (Universidade Federal de São Carlos, 2021)
The aim of this work is to investigate the theme of sexuality in Rousseau's thought. The Genevan philosopher is often accused of paradox and his work of containing problems of unity. These characteristics, however, constitute an advantage to reflect the sexual issue in all its complexity. Rousseau sometimes stands as a defender of morals and virtue, and criticizes the sexual customs of his time, notably in his considerations of romance and theater in the Letter to d'Alembert and in the Preface to Julie, or The New Heloise. Rousseau also considers sexuality to be an important element in his anthropological theory. In the Discourse on Inequality, sex singles out the wild, as it distinguishes it from civilian man and other animals. Together with freedom and perfectibility, sex is a constitutive element of human nature that must be considered in the process of socialization of the species. In Emile, sexuality operates as a kind of catalyst for sociability. Sexual maturity is used by the preceptor as a pedagogical instrument through which he manages the birth of social passions and modulates the student's moral character. Still in Emile, Rousseau elaborates a theory of sexual difference in which the oblique experience of female sexual desire is a fundamental element to understand the union between the sexes in terms of an agreement. Rousseau defends modesty as something natural to women, which makes him one of the authors most criticized by the feminist reception. But Rousseau is a complex author and his work is full of nuances. In The New Heloise, through a female character, Rousseau can question whether the soul has a sex and relativize the sexual difference. In Confessions, by taking the narrative of sexual experience as a privileged place for autobiographical discourse, Rousseau ends up offering a concrete example of an individual in which his relationship with sexuality is more complex than the theory of sexual difference supposes. Still in the autobiographical text, Rousseau reports his passion for botany, a science with which he identifies and which acquires supplement value. If in man, sex is a singularity that becomes more complex and becomes a moral problem, in plants, sex is simple and plural, precisely because it is free from morality. In a nutshell, whether as a critic, as a theorist or as a writer, sexuality is a theme of Rousseau's thought, whose variety of discourses, and even paradoxes, corroborates to reflect the theme in all its complexity.
The paradox of sex: sexuality in Jean-Jacques Rousseau's thought
Keywords: Sexualidade; Sociabilidade; Paradoxo; Rousseau; Sexuality; Sociability; Paradox; CIENCIAS HUMANAS::FILOSOFIA::HISTORIA DA FILOSOFIA